Accuracy of Outpatient Diagnosis Code Based on ICD – 10 - Yeni Tri Utami; Muhammad Amin bin Sahari; Warsi Maryati; Dina Tri Wahyuni (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The accuracy of the diagnostic code plays an important role in the accuracy of the INA-CBG's rates. Outpatient BPJS patient visits at the Astrini Wonogiri General Hospital reached 7,967 patients in 2020, which have superior polyclinics, namely Orthopedic poly and Cardiology poly. Based on a preliminary survey, the percentage of inaccurate in the diagnosis coding for outpatients in the Orthopedic poly reached 90% and the Cardiology poly 30%. The high inaccuracy of the diagnostic code can lead to a decrease in the quality of services in hospitals and affect the sources of reporting information and health service rates. This study aims to determine the accuracy of the outpatient diagnosis code based on ICD 10 at the Astrini Wonogiri General Hospital. This type of research is descriptive with a retrospective approach. The population in this study was 5284 documents, with a sample of 131 documents using the Simple Random Sampling technique. Methods of collecting data by means of observation and interviews. The analysis of the accuracy of this outpatient diagnosis code is interpreted as a percentage. The results of the research on the outpatient diagnosis coding procedure at the Astrini Wonogiri General Hospital in accordance with the SPO, by looking at the Participant Eligibility Letter, Certificate of Evidence of Service, CPPT form (Integrated Patient Progress Record) and Supporting Examination Sheets. The results of the percentage accuracy of the diagnostic code for outpatients in orthopedic poly are 89% (59 DRM) inaccurate codes, 11% (7 DRM) accurate, can be grouped into 2 inaccurate code classifications, namely incorrect code selection and lack of character code additions 5. The percentage accuracy of the diagnosis code for cardiac outpatients is an inaccurate score of 14% (9 DRM), 86% accurate (56 DRM) can be grouped into 2 classifications of inaccurate codes, namely, incorrect code selection and lack of character code additions 4. Factors causing the inaccuracy of the code include the doctor in writing the diagnosis that is not clear so it is difficult to read, the coder doubles as a casemix, assembling and reporting officer, causing a lack of accuracy in reading the sheets containing additional information that support the accuracy of the code. The conclusion from the results of the study is that the inaccuracy of the outpatient diagnosis code at RSU Astrini Wonogiri is still high, so it is necessary to re-socialize related to the SPO for writing diagnoses to doctors, and there is a clear division of job disks so that the coder burden is not too high and more thorough in coding to produce a accurate diagnosis code.